Sanitation and Hygiene Standards in Modern Food Processing: A Four-Year Literature Analysis (2021-2025) - Dimas Andrianto; Zeus Marullah Aswin; Eri Barlian; Elsa Yuniarti; Linda Handayuni (Journal of Innovative and Creativity, 2025)
The study aimed to analyze the evolution of sanitation and hygiene standards in modern food processing industries from 2020 to 2025. This study aimed to identify major trends, technologies, challenges, and best practices that shaped food safety management systems (FSMS), especially under the influence of the COVID-19 pandemic. It also examined the application of wet and dry sanitation methods, their effectiveness, sustainability, and integration with technological innovations such as IoT-based monitoring, nanotechnology antimicrobials, and automated cleaning systems. A systematic literature review was conducted following the PRISMA guideline. Literature searches were performed in Google Scholar for the 2021–2025 period, identifying 350 articles. After screening and eligibility assessments, 30 articles were included for comprehensive analysis. Inclusion criteria focused on peer-reviewed publications discussing sanitation and hygiene in food processing industries. Data extraction covered bibliographic details, sanitation focus, and key findings. The quality of studies was evaluated using the Critical Appraisal Skills Program me (CASP). Data analysis employed thematic, content, and comparative approaches to identify research gaps and trends in sanitation practices. The review found a research surge between 2021 and 2023 driven by the pandemic, emphasizing stricter hygiene practices and digital sanitation monitoring. HACCP, GMP, and ISO 22000 frameworks were dominant in ensuring food safety. Innovative technologies, including cold atmospheric plasma, electrolyzed water, and UV-C LED, emerged as effective and sustainable sanitation tools. Persistent issues included low hygiene compliance, Listeria monocytogenes contamination, and uneven FSMS implementation across sectors. The findings indicate substantial progress in sanitation and hygiene standards through technology adoption and regulatory strengthening. However, consistent implementation, workforce training, and sustainability remain challenges. Continuous innovation and global harmonization of food safety standards are essential for maintaining consumer trust and preventing foodborne diseases. Materials and methods A systematic literature review was conducted following the PRISMA guideline. Literature searches were performed in Google Scholar for the 2021–2025 period, identifying 350 articles. After screening and eligibility assessments, 30 articles were included for comprehensive analysis. Inclusion criteria focused on peer-reviewed publications discussing sanitation and hygiene in food processing industries. Data extraction covered bibliographic details, sanitation focus, and key findings. The quality of studies was evaluated using the Critical Appraisal Skills Program me (CASP). Data analysis employed thematic, content, and comparative approaches to identify research gaps and trends in sanitation practices. Results. The review found a research surge between 2021 and 2023 driven by the pandemic, emphasizing stricter hygiene practices and digital sanitation monitoring. HACCP, GMP, and ISO 22000 frameworks were dominant in ensuring food safety. Innovative technologies, including cold atmospheric plasma, electrolyzed water, and UV-C LED, emerged as effective and sustainable sanitation tools. Persistent issues included low hygiene compliance, Listeria monocytogenes contamination, and uneven FSMS implementation across sectors. Conclusions. The findings indicate substantial progress in sanitation and hygiene standards through technology adoption and regulatory strengthening. However, consistent implementation, workforce training, and sustainability remain challenges. Continuous innovation and global harmonization of food safety standards are essential for maintaining consumer trust and preventing foodborne diseases.